FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN RESUME MEDIS PASIEN RAWAT INAP DI RSUD BATU BARA TAHUN 2021 - Bachtiyar - Wahab; putri khairun nisa; akhmad fatikhus sholikh; desmayanti br surbakti; ripando jhon satria sembiring (Jurnal Penelitian Kesmasy, 2022)
Every hospital is required to maintain medical records. In the medical record there is a medical resume form which is very important to complete, because it contains the entire medical history of the patient. Problems were still found related to filling out incomplete medical resume forms at Batu Bara General Hospital.The purpose of this study was to determine the factors related to the completeness of inpatients medical resume at Batu Bara General Hospital. This type of research used an observational research method by using cross sectional design. The total population were 36 doctors who work at Batu Bara General Hospital.The sampling technique used total sampling. The research instrument was questionnaire and checklist sheet. Data analysis used Chi Square test. The results showed that from 36 doctors, 23 doctors (64%) had knowledge in the good category about filling out medical resume sheets and 13 doctors (36%) had knowledge in the poor category while 27 doctors (75%) had attitudes in the good category. and 9 doctors (25%) had bad attitude.The results of Chi Square test showed that there was significant relationship between doctor's knowledge and the completeness of a medical resume with P value of (0.003) (P-value <0.05) and Prevalence Ratio (PR) = 0.081. Meanwhile, the results of the Chi Square test showed that there was a significant relationship between the attitude of doctor and completeness of medical resume with P value (0.021) (P-value <0.05) and Prevalence Ratio (PR) = 0.200. The hospital should provide understanding and socialization to doctors that it is important to complete medical records, especially on medical resume sheets